2021
DOI: 10.1097/aln.0000000000003877
|View full text |Cite
|
Sign up to set email alerts
|

Cerebral Macro- and Microcirculation during Ephedrine versus Phenylephrine Treatment in Anesthetized Brain Tumor Patients: A Randomized Clinical Trial Using Magnetic Resonance Imaging

Abstract: Background This study compared ephedrine versus phenylephrine treatment on cerebral macro- and microcirculation, measured by cerebral blood flow, and capillary transit time heterogeneity, in anesthetized brain tumor patients. The hypothesis was that capillary transit time heterogeneity in selected brain regions is greater during phenylephrine than during ephedrine, thus reducing cerebral oxygen tension. Methods In this single… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
32
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 27 publications
(33 citation statements)
references
References 45 publications
1
32
0
Order By: Relevance
“…We thank Bombardieri and Tsui 1 for their excellent comments and interest in our study. 2 We agree with Bombardieri and Tsui that the deterioration of microperfusion and possibly tissue oxygenation after phenylephrine administration in the “healthy” brain hemisphere 2 indicates that different vasopressors may also have a different influence on microperfusion and tissue oxygenation in the healthy anesthetized brain and should be further explored. 3 In our opinion, future studies on the effects of different vasopressors on the cerebral macro- and microcirculation should be considered in the context of their different effects on the systemic circulation to provide a fully integrated picture of their influence on organ perfusion and oxygenation.…”
Section: In Replysupporting
confidence: 76%
“…We thank Bombardieri and Tsui 1 for their excellent comments and interest in our study. 2 We agree with Bombardieri and Tsui that the deterioration of microperfusion and possibly tissue oxygenation after phenylephrine administration in the “healthy” brain hemisphere 2 indicates that different vasopressors may also have a different influence on microperfusion and tissue oxygenation in the healthy anesthetized brain and should be further explored. 3 In our opinion, future studies on the effects of different vasopressors on the cerebral macro- and microcirculation should be considered in the context of their different effects on the systemic circulation to provide a fully integrated picture of their influence on organ perfusion and oxygenation.…”
Section: In Replysupporting
confidence: 76%
“…Many researchers in recent times have also reported that the drug ephedrine could be a clinical neuroprotective candidate for treatment of cerebral ischemic stroke 34 and brain injury 35 . Also, ephedrine could exhibit protective effects against chronic obstructive pulmonary disease 36 and one of the standard choices of vasopressor agents to offset the consequences of life-threatening illnesses such as infection, heart failure, and anaphylaxis during surgical procedures 37 , 38 . Owing to its significant impact in medical field, the drug ephedrine is being listed under the WHO’s 21st edition of model list of essential medicines 39 .…”
Section: Introductionmentioning
confidence: 99%
“…In our study, ephedrine was the fi rst-line drug. Koch et al [9] discovered that ephedrine improves brain blood fl ow and tissue oxygenation and may be more eff ective than phenylephrine at improving brain hemodynamics and oxygenation. Thus, we believe that we can omit the infl uence of vasomotor agents on brain saturation, mainly since we analyzed the relationship between rSO2 and MAP.…”
Section: Other Informationmentioning
confidence: 99%